2019
DOI: 10.5327/z2176-947820190462
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação De Metais Tóxicos De Alfaces Cultivadas Em Horta Urbana Na Cidade De São Paulo, São Paulo

Abstract: As hortas urbanas trazem benefícios alimentares e sociais, mas os poluentesatmosféricos são nocivos à saúde. Então, surge a questão: os alimentos dashortas urbanas são seguros? Para investigar, neste estudo utilizou-se a alfacecrespa, a mais consumida em São Paulo e bioindicadora de metais tóxicos.A pesquisa ocorreu de agosto a outubro de 2018, em horta urbana no telhadode um grande shopping da cidade de São Paulo, cercado de intenso tráfego deveículos. Utilizaram-se dois tratamentos, cultivo a céu aberto (T1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The elemental concentrations in lettuce samples were determined by a relative method of Instrumental Neutron Activation Analysis (INAA). INAA, a sensitive, nondestructive, and multi-element technique, has been frequently used to evaluate inorganic contents in different types of matrices, nd applications in the areas of environment, mineralogy, agriculture, health, and archeology (Bortoletto et al 2019;Silva et al 2022).…”
Section: Inaa Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The elemental concentrations in lettuce samples were determined by a relative method of Instrumental Neutron Activation Analysis (INAA). INAA, a sensitive, nondestructive, and multi-element technique, has been frequently used to evaluate inorganic contents in different types of matrices, nd applications in the areas of environment, mineralogy, agriculture, health, and archeology (Bortoletto et al 2019;Silva et al 2022).…”
Section: Inaa Measurementmentioning
confidence: 99%
“…These are required in small quantities, but in excess, they can cause toxic effects (Sharma et Some studies have raised the concern of urban environmental pollution, as for food safety. A recent study in Brazil was conducted in an urban garden on the roof of a large shopping mall in the city of São Paulo, surrounded by heavy vehicular tra c and the mean concentrations of As, Cd, Cr, Pb and Zn in the samples were quanti ed and it was concluded that lettuces grown in an urban garden presented no risk to human health (Bortoletto et al 2019). In China, researchers evaluated hydroponically grown vegetables in a rooftop screen house and the results showed that none of the roof hydroponic vegetables exceeded the maximum residue limit for lead, arsenic, cadmium, chromium, mercury, or nitrate (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%